Public Knowledge, Attitude, and Practice on Herbal Remedies Used During Pregnancy and Lactation in West Bank Palestine - Eid, Ahmad M.; Jaradat, Nidal (Frontiers in Pharmacology, 2020)
The use of herbal products by pregnant and lactating mothers without awareness of their harmful effects may expose both mother and fetus or infant to great dangers, such as abortion, premature delivery, uterine bleeding, and physical and mental retardation of the fetus. Thus, the aim of this study was to investigate the extent to which herbal product treatment is used and the reason for which such products are used, and to ensure that these reasons are correct. An ethnopharmacological survey (cross-sectional observational design study) using a pre-piloted questionnaire was undertaken on herbal products used by pregnant and lactating women in the West Bank area of Palestine. A questionnaire was distributed to 350 pregnant and lactating women. The informed consent forms, ethics, and aims of the present study were reviewed and approved by the Institutional Review Board (IRB) at An-Najah National University. To identify the most important species used, the use-value (UV) index was employed, while the SPSS program was used to analyze the data. Collected data revealed that 13 medicinal plants are utilized, while 12 plants are not used during pregnancy. Moreover, 15 plants are utilized and 9 plants are not used during lactation for treating and dealing with various problems. The most commonly used plants belonged to 14 families, including Lamiaceae, Apiaceae, Leguminosae, and Rubiaceae. The plants most used during pregnancy were sage (Salvia fruticosa), anise (Pimpinella anisum), and peppermint (Mentha × piperita). Castor (Ricinus communis) oil, ginger (Zingiber officinale), saffron (Crocus sativus), and senna (Senna alexandrina) mostly were not used by pregnant women. Moreover, cinnamon (Cinnamomum verum), anise (P. anisum), peppermint (M. piperita), and sage (S. fruticose) were mostly used during lactation. Castor (R. communis) oil, ginger (Z. officinale), garlic (Allium sativum), and aloe (Aloe vera) mostly were not used during lactation. This study is of great importance in order to decrease the possibility of endangering the lives of fetuses and infants. A combined effort among researchers, scientists, lactating women, and pregnant women may help in changing wrong uses and thoughts about medicinal plants and help to improve the overall health of both mother and fetus.